SISTEM PERAWATAN KESEHATAN (BERDUKUN BERBARA) PADA SUKU TALANG MAMAK - Budi Harsono; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Talang Mamak is a set of people who are alienated and still live traditionally in sehiliran Indragiri River , Riau Province . Culture and traditions of the Talang Mamak is very diverse , such as Gawai , Up ponds , even in medicine . Talang Mamak tribe still use traditional medicine in curing the disease , one of them by performing rituals like Berdukun Berbara .Berdukun Berbara is a traditional healing ceremony Talang Mamak tribe with a way to set foot kebara apipanas led by support for the healing of disease . In addition , it aims to reject berdukun custody and keeping the village . Berdukun implemented when there is one of the people who suffer from diseases caused by creature - mahuk smooth or evil spirits . Shamans in treating disease using supernatural power or powers supanatural assisted by spirits good or what they refer to as angels .The study was conducted by qualitative descriptive method and sampling Snowball sampling . The sample consisted of a chief, mind , Stakeholders , and Patients in the village Shaman Jerinjing Talang District of West Rengat Indragiri Hulu .In this study , the authors try to tell and explain how the health care system ( Berdukun Berbara ) tribe in the village Talang Talang Mamak Jerinjing . The results of the interviews and observation of the samples taken researcher , researchers know berdukun treatment system as the game goes on supporting the passage of the treatment , as well as spells and potions which are used for treatment .Furthermore , this study also revealed the existence of social relations , economy and culture between the shaman and the patient . How socio - economic relations and socio- cultural relationships occur in treatment .Keywords : system , health care , traditional medicine , quack .